Análise comparativa do dimensionamento de suportes de linhas de transmissão pela ASCE 10 (1997) e NBR 8800 (2008) - JESUS, Daisirée Silva de (2022)
This project presents a comparative analysis of the design of supports of electric power transmission lines by NBR 8800 (2008) and by ASCE 10 (1997). According to ABNT NBR, 8800 (2008) presents the function of guiding the support scaling for the transmission line in Brazil. However, the software used by the energy sector in Brazil are based on the American standard ASCE 10-97, because of its specificity. For comparison of the standards it was obtained wind of static forces from the criteria of NBR 5422 (1985). The tower design is selected for the freestanding type of suspension of 50.7 meters and for modeling, it was used the SAP2000 software. Then, the requests provided by the software SAP2000 were gathered up and held up scaling in Microsoft Office Excel 2013 program following the design criteria of each standard. Data obtained from the comparative analysis revealed that the tower dimensioned according to the criteria presented in Brazilian Standard profiles obtained from the more robust compression and therefore heavier than the tower scaled by the American Standard. Long, slender metal brackets are more likely to fail before the last resistance load, because they are more susceptible to failure by buckling and wind dynamic actions, causing the structure excessive plastic deformation or instability. ASCE 10 (1997) is a specific provision for this type of structure, as in Brazil, it is recommended the use of NBR 8800 (2008), which aims to direct the design of steel structures and concrete buildings. Because it is a general rule, their restrictions can generate large safety margins for structures that have no housing or employment duties by not look precisely particularities of this type of structure. Therefore, it is essential to further study on transmission lines carriers in Brazil, to be proposed criteria detailed sizing suitable for the specificity of this type of structure.